In vitro antioxidant activity and content of bioactive compounds from Homalomena occulta - Le Thuy, Trang; Le Lam, Son; Nguyen Van, Dung; Ho Xuan, Anh Vu; Nguyen Quang, Man; Tran Thanh, Minh; Tran Thi Van, Thi; Nguyen Viet, Thang; Vo Thi Khanh, Ly; Nguyen Minh, Nhung; Le Trung, Hieu (Hue University Journal of Science: Natural Science, 2024)
Homalomena occulta, a plant widely used in traditional Vietnamese medicine, was assessed for its antioxidant potential through DPPH radical scavenging and total antioxidant capacity methods. The results showed that Homalomena occulta exhibited significant antioxidant activities with a low IC50 value of 40.27 μg/mL, which is comparable to that of curcumin (38.50 μg/mL). Furthermore, the total antioxidant capacity of the Homalomena occulta extract was determined to be 77.48 ± 2.34 mg GA/g. To investigate the composition of the plant, various compounds including total phenolic, total flavonoid, polysaccharides, and triterpenoids were quantified using colorimetric methods with specific reagents. The content of phenolic compounds, flavonoid compounds, polysaccharides, and triterpenoids in Homalomena occulta was found to be 36.87 ± 0.42 GAE/g, 26.83 ± 0.29 mg QUE/g, 5.06 ± 0.06%, and 52.09 ± 1.77 mg Olenanoic/g, respectively. Notably, this study provides the first-ever report on the polysaccharide and total triterpenoid content of Homalomena occulta.